Chất lượng báo cáo tài chính, công bố thông tin và nợ vay của các doanh nghiệp niêm yết Việt Nam - Phan Quynh , Trang; Nguyen Le Ngoc , Anh (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2024)
This study examines the impact of financial reporting quality and information disclosure on firm debt. Using a dataset with 7,174 observations of Vietnamese listed firms during the 2010–2022 period. The Fixed Effect Model (FEM) and Generalized Method of Moments (GMM) regression results show that the quality of financial reporting and the information disclosure have a negative effect on the ratio of total debt to total assets and the use of long-term debt. The findings imply that firms with better reporting quality and information disclosure prefer to use internal funds or equity issuing to debt. This explanation is consistent with the pecking-order theory.
Keywords: Big Four; Financial reporting quality; Information disclosure; Debt